DIPLOMATIC DILEMMA DAN STANDAR GANDA POLITIK AMERIKA SERIKAT TERHADAP KONFLIK SIPIL-MILITER MESIR TAHUN 2013 - Setiawan, Azhari; Saeri, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
United States of America as the main actor—in many cases—of world politics constellation has done a number of double standard politics for preserving its certain national interest. For a century, Middle East has been one of the most focussed object for United States foreign policies. This research is aimed to explain United States diplomatic dilemma and double standard politics toward Egypt civil-military conflict and Morsi coup in 2013, which tries to answer why United States used double standard politics on Egypt case. United States has a strong policy on democratization, human rights and anti-coup, which made a controversial policy on Egypt cases. United States never calls Egypt case as a coup and still continuing its foreign aid to Egypt’s new governement (military government).This research theoretically has built with rasionalism perspectives on International Relations and supported by National Security theories, and also the concept of Diplomatic Dilemma and Double Standard Politics. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Scope of this research is United States policy toward Egypt coup which is considered by viewing international and United States’s middle east allies responses on the same case.Researcher has formulated an answered-hypothesis which reveals the facts that United States double standard is caused by United States diplomatic dilemma. These diplomatic dilemmas also influenced by United States pragmatism on its Arab Spring foreign policy. This research has added one more explanation about United States double standard politics history in Middle East cases for this decade.Keywords : Diplomatic Dilemma, Double Standard Politics, Coup, United States of America, Arab Spring, Middle East.